2012
DOI: 10.1016/j.cgh.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Alanine Aminotransferase Decrease With Age in Longitudinal Analysis

Abstract: Background & Aims An increased level of alanine aminotransferase (ALT) is a marker of liver injury. The mean ALT level has been reported to decrease with age; we performed a longitudinal analysis to determine whether serum levels of ALT changes with age among community-dwelling, older adults in the US. Methods We analyzed clinical data from 2 cohorts of individuals who participated in the Rancho Bernardo Study, in Southern CA. The first cohort comprised 1073 community-dwelling participants (59% women); clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 29 publications
13
36
0
1
Order By: Relevance
“…Our results are consistent with many studies that have shown that elevated liver markers are not only sensitive indicators of hepatobiliary diseases and alcohol consumption, but even within reference range, as in the present study, are associated with a variety of common diseases, such as CAD, AF, DM, dementia, PD [28][29][30][31][32][33], and mortality [34][35][36][37] independently of alcohol consumption. Reported in the literature age and gender-based differences in liver [32,[34][35][36] and bone turnover markers [38][39][40][41][42], as well as in three studied adipokines [43][44][45][46] were confirmed within our study population, specifically, the decrease of transaminase activities and increase of bone turnover (OC and NTx/Cr) with ageing, and higher levels of urinary bone resorption markers and circulating adiponectin and leptin in women than in men.…”
Section: Liver-bone Interactionssupporting
confidence: 81%
See 1 more Smart Citation
“…Our results are consistent with many studies that have shown that elevated liver markers are not only sensitive indicators of hepatobiliary diseases and alcohol consumption, but even within reference range, as in the present study, are associated with a variety of common diseases, such as CAD, AF, DM, dementia, PD [28][29][30][31][32][33], and mortality [34][35][36][37] independently of alcohol consumption. Reported in the literature age and gender-based differences in liver [32,[34][35][36] and bone turnover markers [38][39][40][41][42], as well as in three studied adipokines [43][44][45][46] were confirmed within our study population, specifically, the decrease of transaminase activities and increase of bone turnover (OC and NTx/Cr) with ageing, and higher levels of urinary bone resorption markers and circulating adiponectin and leptin in women than in men.…”
Section: Liver-bone Interactionssupporting
confidence: 81%
“…Reported in the literature age and gender-based differences in liver [32,[34][35][36] and bone turnover markers [38][39][40][41][42], as well as in three studied adipokines [43][44][45][46] were confirmed within our study population, specifically, the decrease of transaminase activities and increase of bone turnover (OC and NTx/Cr) with ageing, and higher levels of urinary bone resorption markers and circulating adiponectin and leptin in women than in men.…”
Section: Liver-bone Interactionssupporting
confidence: 48%
“…Height (meters) and weight (kilogram) were measured, and body mass index (BMI) was calculated as weight in kg divided by height in meter squared (kg/m 2 ). 12,3033 …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, age has been shown to be associated with the ALT level in prior cross-sectional and prospective studies 11-13. Elinav et al 12 reported an inverted curve with peak ALT levels at 40-55 years in a group of Israeli participants.…”
Section: Demographic Characteristics Influence the Serum Alt Levelmentioning
confidence: 96%